2009
DOI: 10.3109/19396360903165256
|View full text |Cite
|
Sign up to set email alerts
|

A Lack of Contact of Sperm with Accessory Sex Gland Secretions Deregulates DNA Methylation and Imprinted Gene Expression in Rodent Embryos

Abstract: Increased oxidative DNA damage is observed in sperm devoid of contact with accessory sex gland (ASG) secretion. After fertilization, these sperm may produce abnormal embryos. In this study, we investigated the possibility that the pattern of DNA methylation and imprinted gene expression in these embryos may be perturbed. Epididymal sperm, uterine sperm, and embryonic day 13 (E13) embryos were collected from hamster and mouse. The extent of global DNA methylation was determined with an antibody against methylcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Just one study has examined SP in this context, reporting a negative correlation between BMI and SP neutral a-glucosidase levels, suggestive of altered epidiymal function (57). Furthermore, the importance of SP for normal sperm methylation has been described (58). Such molecular changes, including gene transcription and the establishment of epigenetic marks, could also be perturbed as a consequence of the environment or disease states such as obesity.…”
Section: Discussionmentioning
confidence: 96%
“…Just one study has examined SP in this context, reporting a negative correlation between BMI and SP neutral a-glucosidase levels, suggestive of altered epidiymal function (57). Furthermore, the importance of SP for normal sperm methylation has been described (58). Such molecular changes, including gene transcription and the establishment of epigenetic marks, could also be perturbed as a consequence of the environment or disease states such as obesity.…”
Section: Discussionmentioning
confidence: 96%
“…In these females, fertilization proceeded normally, but many embryos died during their post-implantation development. Later, it was found that seminal plasma protects spermatozoa from oxidative stress [ 283 ], which may alter the DNA methylation pattern of imprinted genes in embryos [ 284 ]. These reports need further confirmation.…”
Section: Puzzles Of Seminal Plasma and Sperm Competitionmentioning
confidence: 99%